Retorno esperado da evasão fiscal para empresas brasileiras - Lamas, Rodrigo Abrantes (2016)
It presents a stylized model which aims to measure the gain expected by Brazilian companies when they decide to deliberately evade their profits, incurring therefore in some probability of financial loss due to successful enforcement. To verify the adherence of the Brazilian business environment model, needed to the creation of a database containing the historical series of empirical probability of audits by the Receita Federal in domestic companies. Observing the data created and policy actions available based on the own Receita Federal publications, it is concluded that (i) present the probability of a Brazilian company being audited by the Receita Federal is less than 0.5%, (ii) actions recent Receita Federal are aligned with the expected by the inspection agent model and (ii) tax evasion can be seen as a rational investment decision in risky asset when done by 'small taxpayers'.